A Frequency Control Model for Cyber Physical Power System Considering Demand Response Strategy. (July 2018) - Ming, Ni; Qian, Chen; Manli, Li; Qi, Wang; Yi, Tang
Abstract: Due to the increase of power transmission capacity, once an active power vacancy happens, power systems will face a serious frequency instability problem. With the development of communication technology in cyber physical power system (CPPS), demand response (DR) resources can take the initiative to reduce electricity utilization in order to tackle the system under-frequency challenge. This paper presented a frequency control model for CPPS considering DR strategy to rapidly forecast the effects of DR sources participating in frequency control. The model was verified through a case study as well.